Bacterial Skin Infections in Hospitalized Patients with Bullous Pemphigoid. (July 2021) - Li, Furong; Bian, Wenjie; Wu, Yejun; Zhu, Xuejun; Chen, Xixue; Wang, Mingyue
ABSTRACT: OBJECTIVE: To explore the features and risk factors of bacterial skin infections (BSIs) in hospitalized patients with bullous pemphigoid (BP). METHODS: Records were retrospectively reviewed for 110 hospitalized patients with BP admitted to Peking University First Hospital between 2013 and 2019. Bacterial species and drug resistance were assessed, and then the underlying risk factors for BSIs were evaluated. RESULTS: Infections were present in 40% (44/110) of the patients. Staphylococcus aureus (72.7%, 32/44) was the most common bacterium, and it was highly resistant to penicillin (81.3%, 26/32), erythromycin (62.5%, 20/32), and clindamycin (56.3%, 18/32), but 100.0% sensitive to vancomycin and tigecycline. Coronary heart disease ( P = .02; odds ratio [OR], 12.68), multisystem comorbidities ( P = .02; OR, 3.67), hypoalbuminemia ( P = .04; OR, 3.70), high levels of anti-BP180 antibodies (>112.4 U/mL; P = .003; OR, 6.43), and season (spring: reference; summer: P = .002; OR, 23.58; autumn: P = .02; OR, 12.19; winter: P = .02; OR, 13.19) were significantly associated with BSIs. CONCLUSIONS: Hospitalized patients with BP had a high incidence of BSIs, and those patients with underlying risk factors require careful management to prevent and control BSIs.